PRINCIPLES OF COMPILING MEDICAL TERMINOLOGICAL DICTIONARY (Scientific journal of the Fergana State University, 2023)
The article summarizes the need for serious linguistic analysis of medical terms, both quantitatively and qualitatively, and their study from a structural-semantic point of view has become not only one of the current trends in modern terminology, but also one of the most pressing issues of modern terminology.